UMPASA DALAM UPACARA ADAT KEMATIAN SAUR MATUA MASYARAKAT BATAK TOBA DI NAGASARIBU KECAMATAN LINTONGNIHUTA KABUPATEN HUMABANG HASUNDUTAN - Marpaung, Theresia; Jalil, Abdul; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research talked about forms and rhyme of umpasa or maxim on ceremony for the death people who had been saur matua (people whose all their children already got merried) on Tobanese people who lived at Nagasaribu, Lintongnihuta Subdistric, Humbang Hasundutan Regency. This research used kualitative and descriptive metode which was aimed to describe the problem based on reality. This research used death ceremony process for saur matua as the object by using literally datas by doing some interview and classifying the datas which were got from the video of the ceremony. This research finaly got the conclusion that there instruction from umpasa, diksi from umpasa and three forms of umpasa, they were: umpasa with two lines,with the second last umpasa with four lines and the last umpasa with six lines. While there were four roles of umpasa, they were: religious, morality, kinship, conference. And based on the analysis of the data s there were eight rhymes that found on the ceremony, they were: start middle rhyme, finish rhyme, incomplete rhyme, cluster rhyme, uneven rhyme, interlude rhyme, clasp rhyme.Keywords: form umpasa, rhyme